The impact of analysis in the investigation of LBA glass production, transport and exchange and the role of women in this system - Kemp, Victoria (Cranfield University, 2023)
The study of Late Bronze Age (LBA) glasses has developed significantly over the last few decades. The advance of analytical methods capable of the sensitive detection of major, minor and trace elements have enabled researchers in this field to gain a greater understanding of LBA glass compositions in addition to being able to distinguish between glasses manufactured in Egypt and Mesopotamia, the two regions believed to have been the original innovator of glass. This thesis examines a series of LBA glasses excavated from historically significant sites in Egypt, Sinai and the Levant using Laser Ablation Inductively Coupled Mass Spectrometry (LA-ICP-MS). The analysis of unanalysed material from an undisturbed tomb in Gurob, the only confirmed harem palace in Egypt, the temple of Hathor, in Serabit, Sinai and the strategically important site of Tall Zirā’a in the Levant are discussed in this thesis. Early glasses from KV35, the tomb of Amenhotep II (1427-1400 BCE) are examined as part of this thesis: these glasses were previously analysed using scanning electron microscopy; however, this research re-examines the material using LA-ICP-MS, thereby providing trace element data of several colours to determine the provenance of these early royal glasses in addition to presenting trace element data for some of the earliest Egyptian glass colouring strategies. By assessing the strategic importance of the sites in conjunction with the elemental analyses, colouring strategies and provenance of the glasses connected with the sites, this research answers questions about where the first glasses were made and what information the context tells us about the first glasses ever produced. This thesis also readdresses the importance that women played in the transportation and distribution of glass in the LBA. This research also examines the compositional changes in LBA glasses to identify key markers which can be used to date glasses by providing a production era, and consequently indicate the workshops which produced them. Finally, this thesis discusses the control and the volumes of glass moved in the LBA and proposes a model for the LBA glass system.
Braekmans, D. - Associate supervisor
Keywords: Glass; Egypt; Mesopotamia; Laser Ablation Inductively Couple Plasma Mass Spectrometry (LA-ICP-MS); Bronze Age